2018
DOI: 10.1145/3292040.3219674
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotically Optimal Load Balancing Topologies

Abstract: We consider a system of N servers inter-connected by some underlying graph topology G N . Tasks with unit-mean exponential processing times arrive at the various servers as independent Poisson processes of rate λ. Each incoming task is irrevocably assigned to whichever server has the smallest number of tasks among the one where it appears and its neighbors in G N .The above model arises in the context of load balancing in large-scale cloud networks and data centers, and has been extensively investigated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…The expressions for the arrival terms in the derivatives of (15) and the reduced arrival rateλ should be considered more carefully due to the discontinuity at q 00 = 0. We will give a sketch of the derivation of this fluid limit in Subsection 5.2.…”
Section: Fluid Limitmentioning
confidence: 99%
See 4 more Smart Citations
“…The expressions for the arrival terms in the derivatives of (15) and the reduced arrival rateλ should be considered more carefully due to the discontinuity at q 00 = 0. We will give a sketch of the derivation of this fluid limit in Subsection 5.2.…”
Section: Fluid Limitmentioning
confidence: 99%
“…The fluid-limit expression can be validated with simulations of the fluid-scaled stochastic process. Consider for instance Figure 3 where the solution of the fluid limit (15) is presented together with a simulated trajectory of a reasonably large system. It can be observed that the simulated trajectory fluctuates closely around the numerical solution of the fluid limit, which supports the connection between the fluid limit and the behavior of the stochastic system in a many-server setting.…”
Section: Fluid Limitmentioning
confidence: 99%
See 3 more Smart Citations